Utilization of plant secondary metabolites as botanical pesticides in forest plant pests - Yeni Nuraeni; Wida Darwiati (Jurnal GALAM, 2021)
The use of chemical pesticides is often carried out in excessive doses, so that this condition results in increased accumulation of pesticide residues in nature. The residue can kill non target organisms, there was an explosion of secondary pests and pest resistance. One effort to reduce the use of synthetic chemical pesticides is by substitution using botanical pesticides that are more environmentally friendly. Botanical pesticides that are easily biodegradable in nature, so it does not pollute the environment, it is relatively safe for humans and the presence of natural enemies. One of the most potential types of botanical pesticides is from the Meliaceae family, namely neem, mahogany, and suren. In this study, the content of secondary metabolites was tested for neem, mahogany and suren seeds. Toxicity properties against pests conducted through literature searches. The purpose of this study was to obtain information on the toxicity and content of secondary metabolite compounds from the three plant seed extracts against forest pests. The results showed that the extract of neem, mahogany and suren seeds contain compounds secondary metabolites from the saponins, tanins, flavonoids, alkoloids, and terpenoids. The compounds can be used as botanical pesticides to control pests of forest plants.